Microwave drying effect on drying characteristic and energy consumption of Ficus carica Linn leaves - Yilmaz, Pelin; Demirhan, Elcin; Ozbek, Belma (WILEY, 2021)
Ficus carica Linn leaves having significant pharmacological properties such as antioxidant, antifungal, antidiabetic, antibacterial, anti-inflammatory, and anti-pyretic are available just in season. The effective utilization of nutritional values of leaves with enhanced shelf life has gained attention. Drying is usually the preferred technique to eliminate microbial attacks and increase shelf life of seasonal food products. Therefore, in the present study, the effect of microwave drying conditions on effective moisture diffusivity, activation energy, specific energy consumption (SEC), and energy efficiency were investigated at various microwave output power levels and sample amounts. The seven mathematical models were applied to describe the microwave drying kinetics of leaves and Page model was found as the best model. The maximum effective moisture diffusivity and drying rate constant values were determined as 9.84 x 10(-11) m(2)/s and 1.15 1/min, respectively, at microwave output power level of 900 W and sample amount of 20 g. The activation energy values were estimated using the modified Arrhenius equation associated with effective moisture diffusivity (E-a = 11.41 W/g) and drying rate constant (E-a = 8.28 W/g). Additionally, the minimum SEC and maximum energy efficiency values (%) were found as 5.60 MJ/kg water and 40.31, respectively, at microwave output power level of 360 W and sample amount of 100 g. The results obtained from the present study seemed potentially useful to explore the applicability of microwave drying on Ficus carica Linn leaves to expand the availability of leaves having numerous nutritional ingredients throughout the whole year and take the advantage of their benefits in various industries. Practical Applications Even if the benefits of Ficus carica L. leaves have been well presented in various studies in the literature, no study was found particularly which investigated the microwave drying kinetics of these leaves. Apart from the mathematical modeling of the drying characteristic and energy aspects of the leaf samples, the present study also targets to expand the usage area of these leaves with high shelf life and enable people to reach the leaves easily throughout the whole year. Hence, this study has potential for the commercial usage of these leaves for their effective utilization in various industries; such as beverage, bakery, cosmetic, and so on. In that way, the valuable nutritional ingredients of these leaves have been turned in favor of human consumption.
Keywords: ANTIOXIDANT ACTIVITY; HOT-AIR; HEAT-TREATMENT; CELERY LEAVES; KINETICS; EFFICIENCY; CAPACITY; EXTRACTS; QUALITY; EXERGY; Engineering; Food Science & Technology